Impact of Prolonged Spaceflight on Orthostatic Tolerance During Ambulation and Blood Pressure Profiles in Astronauts. Issue 9 (27th August 2019) - Fu, Qi; Shibata, Shigeki; Hastings, Jeffrey L.; Platts, Steven H.; Hamilton, Douglas M.; Bungo, Michael W.; Stenger, Michael B.; Ribeiro, Christine; Adams-Huet, Beverley; Levine, Benjamin D.
Abstract : Background: Astronauts returning to earth usually demonstrate reduced orthostatic tolerance when assessed on a tilt table or quiet standing, but no studies have evaluated postflight orthostatic tolerance during activities of daily living, when it is most clinically relevant. Ambulatory blood pressure (BP) variability also is associated with orthostatic intolerance in certain patient populations and can capture clinically significant orthostatic hypotension during activities of daily living, especially when measured on a beat-to-beat basis. We evaluated the impact of prolonged spaceflight on orthostatic tolerance and BP profiles in astronauts. Methods: Ambulatory beat-to-beat BP was recorded using a portable device for multiple 24-hour time periods before, during, and after 6 months of spaceflight in 12 astronauts (4 women; age 48±5 [mean±SD] years). BP variability in the time domain was calculated as the SD. Systolic BP distribution during activities of daily living was characterized by skewness and kurtosis. Results: In contrast with results from previous studies that used tilt tables or stand tests, no astronaut experienced orthostatic intolerance/hypotension during activities of daily living before or after spaceflight. Also, 24-hour systolic BP decreased in space (120±10 mm Hg before spaceflight versus 106±9 mm Hg during spaceflight; P <0.01), but it returned to normal upon landing (122±13 mm Hg). Diastolic BP was unchanged during and after spaceflight. Systolic and diastolic BP variability remained the same before, during, and after spaceflight (both P >0.05). The skewness of systolic BP increased in space (0.74±0.51 versus 1.43±1.00; P =0.001), indicating that signal fluctuations became asymmetrical; however, it returned to preflight levels after landing (0.51±0.42). The kurtosis increased in space (5.01±7.67 versus 11.10±11.79; P =0.010), suggesting that fluctuations concentrated around the mean with a narrow distribution; however, it also returned to preflight levels (2.21±2.56) after return to earth. Conclusions: Given current countermeasures including in-flight exercise training and volume resuscitation on return, no astronauts experienced orthostatic hypotension or intolerance during routine (for landing day) activities in the initial 24 hours after landing following 6 months in space. Prolonged exposure to spaceflight had little impact on systolic BP variability and its distribution, although the latter showed a transient change in space (accompanied by mild relative hypotension), all of which returned to preflight values after return to earth.